2017 International Conference on Digital Image Computing: Techniques and Applications (DICTA) 2017
DOI: 10.1109/dicta.2017.8227496
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic Reconstruction Using Global Statistical Priors

Abstract: Recent research in tomographic reconstruction is motivated by the need to efficiently recover detailed anatomy from limited measurements. One of the ways to compensate for the increasingly sparse sets of measurements is to exploit the information from templates, i.e., prior data available in the form of already reconstructed, structurally similar images. Towards this, previous work has exploited using a set of global and patch based dictionary priors. In this paper, we propose a global prior to improve both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Having presented the application, we first review the algorithm [20] for a global (unweighted) prior-based reconstruction in Sec. 3.1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Having presented the application, we first review the algorithm [20] for a global (unweighted) prior-based reconstruction in Sec. 3.1.…”
Section: Methodsmentioning
confidence: 99%
“…The latter limitation was relaxed in [18,19] by building dictionary-based priors from multiple templates. However, as reported in [20], dictionary priors are not as accurate and fast as global eigenspace priors. Global eigenspace priors are better able to exploit the similarity of a test volume to a set of templates, by assuming that the new test volume lies within the space spanned by the eigenvectors of the multiple representative templates.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In all of these methods, it is critical and challenging to choose an optimal representative template. Recent work [9][10][11] relaxed the above limitation by building dictionary based and eigenspace based priors. [11] showed that the eigenspace based prior is better able to accommodate the variation in the match of a test volume to a set of templates.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work [9][10][11] relaxed the above limitation by building dictionary based and eigenspace based priors. [11] showed that the eigenspace based prior is better able to accommodate the variation in the match of a test volume to a set of templates. The technique assumed the new test volume lies within the space spanned by the eigenvectors of multiple representative templates, effectively capturing the global properties of this set of templates.…”
Section: Introductionmentioning
confidence: 99%